Exploring the mediating role of flexible working hours in the relationship of supervisor support, job and life satisfaction: A study of female nurses in China - Oscar Dousin; Chen, Xi Wei; Bamini K. P. D. Balakrishnan; Chin, Michelle Chin Lee (Wiley, 2021)
Aims: To examine the mediating role of flexible working hours on the relationship between supervisor support, job and life satisfaction among female nurses in China. Design: A cross-sectional, quantitative study was conducted with online survey questionnaires. Methods: Convenience sampling was implemented with 171 female nurses from two tertiary public hospitals in 2019.Results: The mediation analysis demonstrates that flexible working hours significantly and positively mediate the relationship between supervisor support to job (β= 0.775, p< .001) and life satisfaction (β= 0.745, p< .001). In addition, super-visor support and flexible working hours significantly and positively influence job (r= 0.520, p< .01; r= 0.520, p< .01) and life satisfaction (r= 0. 4 87, p< .01; r= 0. 4 87, p< .01). The study suggested that flexible working hours iarean indicator of what supervisor support (r= 0.656, p< .01) is to improve nurses’ job and life satisfaction. The study revealed that flexible working hours and supervisor support are crucial to female nurses who face high demands at both work and home.